Flux growth and effect of cobalt doping on dielectric, conductivity and relaxation behaviour of 0.91Pb[Zn1/3Nb2/3]O-3-0.09PbTiO(3) crystals - Singh, Budhendra
Crystals of 1 mol% cobalt-doped Pb(Zn1/3Nb2/3)O-3-0.09PbTiO(3) (PZNCT) have been grown using a high-temperature self-flux method. A pure perovskite phase with mixed symmetry at room temperature was observed using X-ray diffraction analysis. Their electrical properties were further investigated by measuring temperature- and frequency-dependent dielectric constant (epsilon) and loss (tan delta) behaviour of as-grown crystals. To study the degree of dielectric relaxation, modified power law fitting and Lorentz-type quadratic fitting were performed. The as-grown PZNCT crystals showed a low Curie temperature (T-c similar to 131 degrees C) with a rhombohedral-tetragonal phase transition temperature (T-rt) of 104 degrees C. The piezoelectric coefficient (d(33)) value at the optimized poling field was found to be similar to 1000 pC N-1. Complete electrical characterization revealed the growth of high-performance PZNCT crystals with enhanced remnant polarization (34.23 mu C cm(-2)) and low coercive field (6.97 kV cm(-1)) with cobalt doping. The conduction and relaxation mechanisms of grown PZNCT crystals have been discussed in detail.